Use and misuse of instant messaging in clinical data sharing: the EHRA-SMS survey. Issue 8 (12th March 2021) - Guerra, Federico; Linz, Dominik; Garcia, Rodrigue; Kommata, Varvara; Kosiuk, Jedrzej; Chun, Julian; Boveda, Serge; Duncker, David
Abstract: Instant messaging (IM) enables medical professionals to quickly share clinical data to their peers for counselling. Purpose of this survey is to assess the habits related to IM, their application in clinical practice and the perceived pros and cons. An online survey was distributed to the medical community via newsletters, Twitter, LinkedIn, and Facebook. The survey consisted of 22 questions made on an individual-basis and collected anonymously on SurveyMonkey. A total of 287 subjects from 33 countries responded to the survey (mean age 43 years, 74.8% male). Of all respondents, 88.3% routinely send and 90.3% receive clinical data through IM which was second only to face-to-face contact as the preferred method for sharing clinical data. Twelve-lead electrocardiograms (88.6%), medical history (61.4%), and echo loops (55.7%) were the data shared most often. Nearly half of the clinical data that are sent (43%) or received (44%) are not anonymized. In the same way, 29.3% of the respondents were not aware of the European General Data Protection Regulation (GDPR) at the time of the survey. IM apps are used by medical professionals worldwide to share and discuss clinical data and are preferred to many other methods of data sharing, being second only to face-to-face contact. IM are often used to share many different types of clinical data, being perceived as a fast and easy way of communication. Medical professionals should be aware of the appropriate use of IM to prevent legal and privacy issues.